a = -1
b = -9
c = -1/8
Step-by-step explanation:
The given polynomial:
![(-1)/(8)\text{ - 9x }-x^2](https://img.qammunity.org/2023/formulas/mathematics/college/osx787h2y5qsl8dckwcpb4fuaqkw402707.png)
Rewritting in the form:
![\begin{gathered} ax^2\text{ + bx + c} \\ -x^2\text{ - 9x -}(1)/(8) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ck5sgroad0vr5vehfhkow3uo4d8bfrhr9w.png)
where a is the coefficient of x²
b is the coefficient of x
c is the constant (only number)
Comparing both equation:
ax² = -x²
If you divide through by x², a = -1
a = -1
bx = -9x
if you divide through by x, b = -9
b = -9
c = -1/8